Strategies for the functionalisation of gold nanorods to reduce toxicity and aid clinical translation - Shi,X; Perry,H; Wilton-Ely,J (Nanotheranostics, 2021)
Gold nanorods (GNRs) show great promise as photothermal therapy agents due to their remarkable ability to convert light into heat. In most cases, gold nanorods are synthesised via a seed-mediated method assisted by surfactants. However, the toxicity of these surfactants, principally cetrimonium ions, has prevented GNRs from being used more widely in vivo. To address this issue, various detoxification and functionalisation approaches have been proposed in recent years to replace or cover surfactant coatings on the gold surface. In this short review, the advantages and limitations of each approach are examined in the context of the recent progress made towards the design of GNRs suitable for use in the body.